UPGRADE SCIENCE AND TECHNOLOGY INDEX (SINTA) WORKSHOP FOR RESEARCH FACILITIES AND COMMUNITY SERVICE AND SCORE IMPROVEMENT IN THE FRAMEWORK OF CLUSTERIZATION - Frezy Paputungan (Journal of Hulonthalo Service Society (JHSS), 2022)
Sinta is an indexing journal portal managed by the Ministry of Education and Culture of the Republic of Indonesia. There are also those who say that Sinta is a database for the National Journal which has been accredited by Arjuna. Sinta is a web-based research information system that offers fast, easy and comprehensive access to measure the performance of researchers, institutions and journals in Indonesia. With SINTA access to research data on PTS throughout Indonesia is open, this can also determine the quality of Private Higher Education which is then known as clustering. Private Higher Education Clusterization is very important, considering that the quality and quantity of IKU PT emphasizes research and community service. This research was conducted to determine the success of implementing the SINTA workshop for lecturers at UBMG. The workshop was held for one day in the AULA of the UBMG campus, with participants from all lecturers at Bina Mandiri University, Gorontalo and 62 people participating. In practice, the resource persons provided training on how to register for SINTA, upgrade (from profiles, Google, WOS, Garuda and so on). Lecturers at the Bina Mandiri University of Gorontalo participated in this workshop with enthusiasm, until the implementation of the activities was completed in the afternoon. After the implementation of the SINTA upgrade workshop, Lecturer's SINTA score rose to be able to boost UBMG's score past other well-known universities. From 620 it rose to 720, the score of UBMG skyrocketed and increased within one month.